2018
DOI: 10.20944/preprints201808.0193.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence the Fillers Orientation: A Short Review

Abstract: Bipolar plates significantly contribute in the development of the polymer electrolyte membrane (PEM) fuel cells technology due to their ability to produce high electrical conductivity based on type of materials used. Mismatching of inappropriate materials and manufacture may lead to the inferior performance of PEM fuel cells. Hence, material development was determined crucial to balance the overall performance of PEM fuels including the mechanical properties and electrical conductivity of the materials. Studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Miyaska, et al, [1] appear to be essentially the first to present evidence of a thermodynamic influence on the percolation threshold in electrical conductivity measurements with carbon fillers as indicated in Fig. 1 and Several review authors [2][3][4][5][6][7][8][9][10][11] have found that many models have been proposed to characterize the percolation threshold as indicated by the sharp increase in the S shaped curves described adequately with the data of Miyaska et al, [1] for several carbon filled composites as indicated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Miyaska, et al, [1] appear to be essentially the first to present evidence of a thermodynamic influence on the percolation threshold in electrical conductivity measurements with carbon fillers as indicated in Fig. 1 and Several review authors [2][3][4][5][6][7][8][9][10][11] have found that many models have been proposed to characterize the percolation threshold as indicated by the sharp increase in the S shaped curves described adequately with the data of Miyaska et al, [1] for several carbon filled composites as indicated in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…8 also revealed that the HDPE/EP/SG composites exhibit lower resistivity anisotropy compared to the PP/EP/SG composites at the same SG contents. This is due to the lower viscosity of HDPE compared to PP, which would promote more random orientation of the filler during melt mixing [50].…”
mentioning
confidence: 99%